KOLABORASI ETIS GURU DAN ORANG TUA DALAM EKOSISTEM PEMBELAJARAN DIGITAL: TANTANGAN DAN STRATEGI PENGUATAN KEMITRAAN - Indah Sari, Nur; Asri Angellina, Dhika; Lutfiyana, Rizqy; Muhlisin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Ethical collaboration between teachers and parents in the digital learning ecosystem is a crucial factor that remains underexplored in Indonesian educational research. Most previous studies discuss parental involvement in general terms, but research on the ethical dimensions of digital communication between teachers and parents remains very limited. This article aims to analyze the challenges and strategies for strengthening the ethical partnership between teachers and parents in the digital learning ecosystem, particularly at the early childhood education (ECE) level. The method used is library research with a descriptive qualitative approach, reviewing scientific journals, books, and educational policy documents. Data analysis was conducted using content analysis. The results show that the main challenges include: (1) digital literacy gaps between teachers and parents; (2) inconsistency in technology use rules between home and school; (3) weak communication ethics in digital platforms; and (4) limited technological infrastructure. As a theoretical contribution, this article proposes the Digital Ethical Partnership (DEP) framework, integrating principles of transparency, mutual respect, confidentiality, and active participation in technology-based teacher-parent communication. Practical implications include the importance of developing school digital communication SOPs, digital parenting programs, and classroom digital group codes of ethics